2022
DOI: 10.1021/acs.joc.2c02442
|View full text |Cite
|
Sign up to set email alerts
|

Baccaramiones A–D, Four Highly Oxygenated and Rearranged Trinorditerpenoids from Baccaurea ramiflora

Abstract: Baccaramiones A–D (1–4), four highly oxygenated and rearranged trinorditerpenoids, were isolated from Baccaurea ramiflora. Compound 1 is a 1(10 → 5)-abeo-15,16,17-trinor-ent-abietane featuring a unique 5/6/6 spirocyclic scaffold, and 2–4 are the first example of a novel 20(10 → 5)-abeo-15,16,17-trinor-ent-abietane skeleton. Their structures were established by spectroscopic analysis, X-ray crystallography, and electronic circular dichroism calculations. A plausible biosynthetic pathway for 1–4 was proposed. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Compounds 100 , 477 , and 473 exhibited inhibitory effects on concanavalin A-induced T cell proliferation (IC 50 = 13.6, 1.66, and 2.09 μM, respectively), as well as lipopolysaccharide-induced B cell proliferation (IC 50 = 22.4, 1.37, and 3.31 μM, respectively), without exhibiting any obvious cytotoxicity to T cells and B cells [ 37 , 146 ]. Compounds 258 and 261 showed strong inhibitory activities against Con A-induced T lymphocyte proliferation, with IC 50 values of 23.7 and 8.69 μM, respectively.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Compounds 100 , 477 , and 473 exhibited inhibitory effects on concanavalin A-induced T cell proliferation (IC 50 = 13.6, 1.66, and 2.09 μM, respectively), as well as lipopolysaccharide-induced B cell proliferation (IC 50 = 22.4, 1.37, and 3.31 μM, respectively), without exhibiting any obvious cytotoxicity to T cells and B cells [ 37 , 146 ]. Compounds 258 and 261 showed strong inhibitory activities against Con A-induced T lymphocyte proliferation, with IC 50 values of 23.7 and 8.69 μM, respectively.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…The in vitro evaluation of immunosuppressive activity was carried out using the protocol described previously (Chen et al, 2023;Ren et al, 2022;Zhou et al, 2023), and cyclosporin A was used as the positive control. The MTT assay was used to determine the cytotoxicity against murine splenocytes, while the murine lymphocyte proliferation induced by ConA (1 μg/mL) or LPS (10 μg/mL) were assessed by 3 H thymidine incorporation.…”
Section: Immunosuppression Assaymentioning
confidence: 99%
“…Therefore, the search for naturally occurring novel immunosuppressants is of significant medical interest. In our continuing search for novel immunosuppressants from natural source (Chen et al, 2023;Ren et al, 2022;Zhou et al, 2023), compounds 1−4 and 6−8 were evaluated for their inhibitory effects on the concanavalin A (ConA)induced proliferation of T lymphocytes and lipopolysaccharide (LPS)-induced proliferation of B lymphocytes in vitro. The results revealed that compounds 2 and 6 demonstrated mild immunosuppressive activities against T and B cells, with IC50 values varying from 24.2 to 38.8 μM, and no signs of toxicity (Table 4).…”
Section: Introductionmentioning
confidence: 99%
“…Diterpenoid natural products are biosynthetically derived from geranylgeranyl diphosphate, which undergoes a series of rearrangements and/or cyclizations to produce more types of diterpenoids. , Their intriguing structures and broad bioactivities have been reported. , Among them, 6/6/6 tricyclic diterpenoids with a gem-dimethyl unit in one ring, such as abietane, cassane, pimarane, cleistanthane, and podocarpane diterpenoids, are several important subclasses. Their structural changes were mainly reflected in ring-opening or carbon reduction (Figure ), such as 3,4- seco -cleistanthane. However, novel type diterpenoids derived from the above class via rearrangements are rarely been reported, unlike lathyrane diterpenoids.…”
Section: Introductionmentioning
confidence: 99%
“…Their structural changes were mainly reflected in ring-opening or carbon reduction (Figure 1), such as 3,4-seco-cleistanthane. 5−7 However, novel type diterpenoids derived from the above class via rearrangements 8 are rarely been reported, unlike lathyrane diterpenoids.…”
Section: ■ Introductionmentioning
confidence: 99%